2021
DOI: 10.3390/a14040125
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Implicit Representation of Volumetric Shells with Predefined Thickness

Abstract: We propose and validate a method to find an implicit representation of a surface placed at a distance h from another implicit surface. With two such surfaces on either side of the original surface, a volumetric shell of predefined thickness can be obtained. The usability of the proposed method is demonstrated through providing solid models of triply periodic minimal surface (TPMS) geometries with a predefined constant and variable thickness. The method has an adjustable order of convergence. If applied to surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For FKS, we added the gradient of Equation ( 2) and multiplied it by k, as shown in Equation (3). Geier et al proposed a method of surface offsetting with significantly reduced line spacing variance by adding the magnitude of the gradient vector of the surface to the original implicit function [61]. This method works because the gradient is a proxy for the normal of a surface and it can be shown that the gradient and normal vectors are coaxial.…”
Section: Creating a Flexible Customizable 3d Tpms Model For Btementioning
confidence: 99%
“…For FKS, we added the gradient of Equation ( 2) and multiplied it by k, as shown in Equation (3). Geier et al proposed a method of surface offsetting with significantly reduced line spacing variance by adding the magnitude of the gradient vector of the surface to the original implicit function [61]. This method works because the gradient is a proxy for the normal of a surface and it can be shown that the gradient and normal vectors are coaxial.…”
Section: Creating a Flexible Customizable 3d Tpms Model For Btementioning
confidence: 99%